NUTRITIONAL KNOWLEDGE, GENETICS, OBESITY, AND EDUCATION: RISK FACTORS FOR TYPE 2 DIABETES AT SARANPANDANG - Barus, Brigita Charvio; Aprianti Lubis, Nenni Dwi; Ichwan, M; Panggabean, Merina (UNG, 2026)
Type 2 Diabetes Mellitus (T2DM) represents a persistent global public health challenge, particularly in low and middle income countries where early detection and preventive efforts remain limited. This study aims to examine the associations between nutritional knowledge, genetic predisposition, nutritional status, and educational attainment with the risk of T2DM among adults residing in the service area of Puskesmas Saranpadang, Kabupaten Simalungun. Employing an analytical cross-sectional design, the study involved 94 adults aged 45–55 years selected through purposive sampling. Nutritional knowledge was evaluated using a standardized and validated questionnaire, while random blood glucose levels (RBGL) were measured to identify individuals at risk, with RBGL ≥ 200 mg/dL classified as “at risk.” Data were analyzed using the Chi-square test, with statistical significance determined at P-value 0.05. The results demonstrated significant associations between T2DM risk and educational level (P-value = 0.003), nutritional knowledge (P-value = 0.001), genetic history (P-value = 0.001), and nutritional status based on body mass index (P-value = 0.001). Participants with limited nutritional knowledge, positive familial diabetes history, and elevated BMI exhibited a higher likelihood of being at risk for T2DM. Lower educational attainment was further associated with reduced health literacy and suboptimal lifestyle practices. The novelty of this study lies in its comprehensive analysis of multiple interacting risk factors using RBGL screening within a primary healthcare context. These findings underscore the importance of strengthening community-based prevention strategies, particularly through targeted health education and early screening programs, to mitigate the rising burden of T2DM in resource-limited settings.